Analisis Relevansi Nilai Capital Expenditure Pada Siklus Hidup Perusahaan Yang Berbeda - Widya Syamita; Nurzi Sebrina (Universitas Negeri Padang, 2019)
This study aims to provide empirical evidence regarding the analysis of the value relevance of capital expenditure on the company’s life cycle in manufacturing companies listed on the Indonesian Stock Exchange in 2013-2017. By using purposive sampling method, there were 88 companies as the research’s sample. Stock return variable are measured using marked adjusted model, and capital expenditure variable are measured using capital expenditure changes (CAPCH) and life cycle firm are measured using cash flow patterns. The type of data used is secondary data obtained from www.idx.co.id and used is panel regression analysis. The results of this study show that capital expenditure information has no value relevance for investors and capital expenditure information does not have a higher value relevance during the stage of start up, growth, mature compared to the decline stage